Effect of methylphenidate on oculomotor function in individuals with multiple sclerosis: a pilot randomized placebo-controlled trial - Rich, Timothy J.; Alexander, Aubree; Dobryakova, Ekaterina; Chiaravalloti, Nancy D.; DeLuca, John; Costa, Silvana L (Frontiers in Neurology, 2024)
Individuals with multiple sclerosis (MS) frequently experience visual and oculomotor symptoms that may impact and confound neuropsychological assessments of information processing speed (IPS). In this study, we examined the effect of the psychostimulant methylphenidate on oculomotor function in a sample of 11 participants with MS using a repeated measures crossover design. In addition, we explored the association between change in oculomotor speed and change in information processing speed. We found a significant improvement in oculomotor speed in the methylphenidate condition as compared to placebo. This improvement was significantly correlated with improvement on a visuomotor assessment of IPS (Symbol Digit Modalities Test), but no such association was found for an auditory-verbal assessment of IPS (Paced Auditory Serial Addition Test). These findings suggest that individuals with MS experience improved oculomotor speed while taking methylphenidate, which may, in turn, improve performance on assessments of IPS with visuomotor demands.